1997
DOI: 10.1042/bj3270095
|View full text |Cite
|
Sign up to set email alerts
|

Functional diversity and interactions between the repeat domains of rat intestinal lactase

Abstract: Lactase-phlorizin hydrolase (LPH), a major digestive enzyme in the small intestine of newborns, is synthesized as a highmolecular-mass precursor comprising four tandemly repeated domains. Proteolytic cleavage of the precursor liberates the pro segment (LPHα) corresponding to domains I and II and devoid of known enzymic function. The mature enzyme (LPHβ) comprises domains III and IV and is anchored in the brush border membrane via a C-terminal hydrophobic segment. To analyse the roles of the different domains o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
1

Year Published

1998
1998
2003
2003

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 53 publications
(57 reference statements)
1
23
0
1
Order By: Relevance
“…In this process, the outside of the plasma membrane becomes the exposed surface on the fat globule 27 , so that lactase is protruding from the globule into the aqueous phase of milk. Although without effect on lactase activity, the LPH precursor is not proteolyticaly processed in the mammary gland, as in transfected COS cells [14][15][16] but unlike intestinal cells 12,13,25 . This is probably related to the absence in mammary cells of an as-yet uncharacterized, intestinal-specific processing enzyme.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In this process, the outside of the plasma membrane becomes the exposed surface on the fat globule 27 , so that lactase is protruding from the globule into the aqueous phase of milk. Although without effect on lactase activity, the LPH precursor is not proteolyticaly processed in the mammary gland, as in transfected COS cells [14][15][16] but unlike intestinal cells 12,13,25 . This is probably related to the absence in mammary cells of an as-yet uncharacterized, intestinal-specific processing enzyme.…”
Section: Discussionmentioning
confidence: 99%
“…First, the use of the ␣Lc promoter instead of another mammaryspecific promoter is thought to allow LPH synthesis in those cells that produce lactose by the lactose synthetase complex 19 ; this property is important if the same approach is used in the case of dairy cattle, as these animals exhibit a heterogenous cellular expression of milk proteins 20 . Second, LPH, which is synthesized as a fully active and transport-competent precursor [14][15][16] , is the most efficient enzyme to hydrolyze lactose, as compared with other common ␤-glycosidases such as the product of the Escherichia coli lacZ gene. Third, LPH is membrane bound and is likely to be sorted via the same route as lactose synthetase, so that lactose hydrolysis may already start intracellularly within the secretory vesicles in which lactose is concentrated 21 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The enzyme has two activities (EC 3.2.1.23, 3.2.1.62), a β-galactosidase activity hydrolysing lactose, and a β-glucosidase activity (Wacker et al 1992;Zecca et al 1998;Arribas et al 2000) capable of hydrolysing phlorizin, a disaccharide found in roots and bark of plants of the family Rosacaeae and some seaweeds. The mature lactase-phlorizin hydrolase enzyme contains two related domains harbouring the two active sites (Arribas et al 2000), but at least in rats it appears that both domains need to be present to allow lactase activity (Jost et al 1997). Lactase-phlorizin hydrolase can also hydrolyse other plant glycosides such as flavonoid glycosides (Day et al 2000) and pyridoxine-5Ј-β-D-glucoside (Armada et al 2002;Mackey et al 2002), apparently using the lactose active site.…”
Section: Congenital Alactasia and Adult Hypolactasiamentioning
confidence: 99%